Preservation of Sarawak Ethnic Languages : The Sarawak Language Technology (SaL 1) Initiative - Yoe, Alvin W.; Saee, Suhaila; Sarah, Flora; Jali, Nurfauza; Suriati, Khartini; Mit, Edwin; Ting, Su Hie; Wilfred, Jennifer; Ng, Giap Weng (2008)
The population of speakers of indigenous languages all over the world is decreasing. This drop in numbers is due to the pressures of dominant global languages (such as English which is the lingua franca of international commerce, research, and the Internet), rural-urban migration, and exogamy (inter-ethnic group marriages). Similarly, the number of speakers of Sarawak's 63 languages is also declining. Thus, the Sarawak Language Technologies (SaLT) Research Group at Universiti Malaysia Sarawak has initiated a number of research and development projects with the end goal of revitalising and maintaining the ethnic languages of Sarawak. The ongoing projects include building corpora of languages (Iban, Melanau, and Kelabit), as well as, research and development of technologies whic!1 contribute to the implementation of software· for the ethnic languages. Specifically, these projects include development of morphological analysers and Part of Speech (POS) taggers which ad